Sports - Li, Xuwu (Understanding Chinese culture, 2018)
Chapter 8, “Sports,” by Li Xuwu and translated by Xue Ping, offers a comprehensive coverage of the genesis, evolution, and modernization of sport in China. It focuses on martial arts, the introduction of Western sports, mass sports, school physical education, and Chinese achievements in modern competitive sports.